2020
DOI: 10.3389/fneur.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects and Mechanisms of Apelin/APJ System on Ischemic Stroke: A Promising Therapeutic Target

Abstract: The orphan receptor APJ and its endogenous ligand apelin, which are expressed in the brain, are the major components of the apelin/APJ system. Growing evidence shows that the apelin/APJ system plays a vital role in the pathophysiology of cerebral ischemic injury. Targeting the apelin/APJ system may have protective effects on cerebral ischemic injury. In this review, we sum up the latest research progress relating to the actions and therapeutic potential of the apelin/APJ system in ischemic stroke. An in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 100 publications
(127 reference statements)
0
9
0
2
Order By: Relevance
“…Він був відкритий у 1992 році і вважається адипокіном, так як секретується адипоцитами людини. Апелін та його рецептори (зокрема G-білковий рецептор апеліну, стара назва -APG-рецептор) в високих концентраціях були виявленні в кардіоміоцитах, ендотелії судин, клітинах гладенької мускулатури, головному мозку, нирках та наднирниках [1,8,17]. Рецептори апеліну регулюють багаточисельні біологічні функції і приймають участь в підтриманні серцево-судинного і метабол-ічного гомеостазу [4,11].…”
Section: вступunclassified
See 1 more Smart Citation
“…Він був відкритий у 1992 році і вважається адипокіном, так як секретується адипоцитами людини. Апелін та його рецептори (зокрема G-білковий рецептор апеліну, стара назва -APG-рецептор) в високих концентраціях були виявленні в кардіоміоцитах, ендотелії судин, клітинах гладенької мускулатури, головному мозку, нирках та наднирниках [1,8,17]. Рецептори апеліну регулюють багаточисельні біологічні функції і приймають участь в підтриманні серцево-судинного і метабол-ічного гомеостазу [4,11].…”
Section: вступunclassified
“…Встановлено, що рівень апеліну суттєво знижується вже на другу добу у пацієнтів з гострим інфарктом міокарда та у хворих на ішемічний інсульт. Слід зазначити, що рівень апеліну значно нижчий у курців в порівнянні з тими, хто немає цієї шкідливої звички [8,17,21] [3,14,20].…”
Section: вступunclassified
“…APELA is a novel endogenous peptide ligand that activates the APJ receptor axis and is cardioprotective against HTN, MI, pulmonary arterial hypertension, and heart failure [37,38]. Recently, studies have shown that the apelin/APJ axis possess neuroprotective effects by inhibiting neuronal apoptosis and improving functional recovery in IS through diverse mechanisms, including suppressing inflammatory responses, modulating autophagy, and promoting angiogenesis [39]. MARCH1 has been identified as a susceptibility locus for MI and HTN in Japanese [40], and regarding IS, was included as 1 of the 31 SNPs significantly associated with IS in an initial EWAS [41].…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery as the second endogenous ligand of the APJ receptor (Szokodi et al, 2002), Elabela has received growing interest given the pharmacological role of the Apelin-APJ system in a variety of physiological and pathological processes, which include cardiovascular and kidney diseases, but also metabolic disorders, such as insulin resistance/type 2 diabetes and obesity, cancer development and progression, ischemic stroke as well as neurodegenerative diseases (Scimia et al, 2012;Chen et al, 2018;Coquerel et al, 2018;Wysocka et al, 2018;Castan-Laurell et al, 2019;Huang et al, 2019;Kinjo et al, 2020;Luo et al, 2020;Masoumi et al, 2020;Tian et al, 2020). In particular, similar to Ape13, Elabela which binds to APJ and activates the β-arrestin-2 and G αi signaling pathways exerts protective effects against various cardiovascular diseases and related complications (Coquerel et al, 2018;Kuba et al, 2019;Liu et al, 2019;Chen et al, 2020a;Liu et al, 2020;Ma et al, 2020;Xu, 2020).…”
Section: Discussionmentioning
confidence: 99%